2010
DOI: 10.1161/circimaging.109.880625
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Prognostic Value of Coronary CT Angiography in Patients With Suspected Coronary Artery Disease

Abstract: Background-Multidetector CT coronary angiography (MDCTCA) is capable of detecting coronary artery disease (CAD) with a high diagnostic accuracy. In particular, this technique is credited with having a negative predictive value close to 100%. However, data about the prognostic value of MDCTCA are currently lacking. We sought to determine the prognostic value of MDCTCA in patients with suspected but undocumented CAD and, in particular, the incremental prognostic value as compared with clinical risk and calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 38 publications
4
63
0
1
Order By: Relevance
“…Although the diagnostic accuracy of cCTA has been reported in many studies, its practical value to predict clinical events is less defined (31). However, Russo et al (32) recently reported that CACS and cCTA findings, such as obstructive CAD and presence of noncalcified or mixed plaques, were predictors of a coronary event. In this study, 60% of the study subjects were asymptomatic and about 70% were classified as intermediate risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diagnostic accuracy of cCTA has been reported in many studies, its practical value to predict clinical events is less defined (31). However, Russo et al (32) recently reported that CACS and cCTA findings, such as obstructive CAD and presence of noncalcified or mixed plaques, were predictors of a coronary event. In this study, 60% of the study subjects were asymptomatic and about 70% were classified as intermediate risk.…”
Section: Discussionmentioning
confidence: 99%
“…During a three-year follow-up of cases with a CAC score of zero, Uretsky et al (18) reported a mortality rate of 0.4%, and the deaths occurred among cases without plaques detected in coronary CT angiography. In 2010, Russo et al (5) found that the occurrence of cardiovascular events in cases with noncalcified or mixed type plaques was higher compared with cases that had a CAC score above 400. Therefore, comprehensive prognostic studies need to be performed in the future to determine whether coronary atherosclerosis can be excluded in cases with a CAC score of zero, whether the presence of noncalcified plaque would increase the rate of cardiac events in these cases, and whether plaque detection has clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies that were conducted in this field, electron beam CT was used in a limited number of centers and was costly; therefore, the CAC score was not accepted for widespread use (4). However, the implementation of multidetector CT at the end of the 1990s resulted in the widespread use of CAC scoring (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28 We also found a significant association between lower plasma HMW adiponectin and the presence of NCP. Previous CTA studies documented that the presence of NCP, regardless of stenotic severity in lesions, was the strongest predictor of acute cardiac events 29 and that the number of NCP with a calcified component (namely, mixed plaques) was an independent predictor of acute cardiac events. 30 Broedl et al suggested that serum adiponectin was an independent predictor of NCP as assessed by CTA and might thus contribute to coronary plaque vulnerability.…”
Section: Hmw Adiponectin Concentrations and Coronary Atherosclerosismentioning
confidence: 93%